Absorption of NH3 on pristine and defected boron nitride nanosheets: A first principle study. (December 2015) - Li, Hui; Chen, Zheng; Fang, Xiaoliang; Tie, Deyou
Abstract: Versatile functional groups can be connected to Boron Nitride nanosheet (BNNS) through Lewis acid/base interaction for targeted applications. However, there have been few experimental reports about Lewis acid attack at the N atoms on BNNS, so far as we see. VdW-DFT is employed in this paper to investigate the interaction between NH3 representing Lewis base and pristine or defected BNNS. Comparing the binding energy, separation and charge distribution of NH3 and pristine or defected BNNS systems, the distinctive defect in BNNS is found to be the key role in the absorption progress. Thus, it is supposed that the missing of Lewis acid and BNNS complex can be attributed to the absence of N vacancies and B-edges in BNNS. Highlights: Only Lewis base groups can be attached on boron nitride nanosheets. Defects in boron nitride nanosheets have significant effects on its functionalization. Dominating zigzag N edge defects were found in boron nitride nanosheets. Dominating zigzag N edge defects in boron nitride nanosheets lead to is Lewis base functional groups.